What Is Religious Authority? : Cultivating Islamic Communities in Indonesia - Alatas, Ismail Fajrie, 1983- (Book collections on Project MUSE., 2021)
"Our shared understanding of religious authority owes much to the classic writings of sociologist Max Weber over a century ago, and in particular to Weber's articulation of charismatic leadership. In this book about the nature of religious authority in a majority Muslim society, Ismail Fajrie Alatas breaks with the Weberian model. He argues that religious authority emanates neither from the charismatic aura of gifted leaders nor to the ways in which such leaders master texts or scriptures deemed foundational by religious tradition. Alatas's core argument is that such authority is always constituted through the ceaseless work of community-building. By "community building," Alatas refers to an on-going process of networking, institution-building, counselling, trouble-shooting, advocating, fund-raising and ritual organizing, all with the aim of aligning the community to a foundational past -- to the imagined early days of the religious tradition in question"--